Genome-wide identification of the PFK gene family and their expression analysis in Quercus rubra - Kim, Tae-Lim; Lim, Hyemin; Denison, Michael Immanuel Jesse; Natarajan, Sathishkumar; Oh, Changyoung (Frontiers in Genetics, 2023)
The glycolytic pathway involves phosphofructokinase (PFK), a rate-limiting enzyme that catalyzes the phosphorylation of fructose-6-phosphate. In plants, the two PFK members are ATP-dependent phosphofructokinase (PFK) and pyrophosphate-fructose-6-phosphate phosphotransferase (PFP). However, the functions of the PFK family members in Quercus rubra are not well understood. The purpose of this study was to investigate the genome-wide distribution of the PFK family members and their roles in Q. rubra by performing a systematic study of the phylogenetic relationships, molecular characteristics, motifs, chromosomal and subcellular locations, and cis-elements of QrPFKs. We identified 14 QrPFK genes in the genome of Q. rubra, followed by examining their expression in different tissues, including the roots, stems, and leaves. The phylogenetic tree divided the 14 QrPFK genes into two groups: 11 belonging to PFK and three belonging to PFP. The expression profiles of all 14 proteins were relatively the same in leaves but differed between stems and roots. Four genes (Qurub.02G189400.1, Qurub.02G189400.2, Qurub.09G134300.1, and, Qurub.09G134300.2) were expressed at very low levels in both stems and roots, while two (Qurub.05G235500.1 and Qurub.05G235500.1) were expressed at low levels and the others showed relatively high expression in all tissues.We corrected it.phosphate phosphotransferase (PFP EC 1.7.1.90), another form of PFK, using pyrophosphate rather than ATP as a phosphoryl donor. PFP catalyzes this process and reaches near equilibrium in both directions, unlike PFK, which is nearly irreversible in vivo.PFP has been well characterized at the molecular and biochemical levels in all three domains of life since the discovery of the first